If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -4 = -15 Reorder the terms: -4 + -1x = -15 Solving -4 + -1x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = -15 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = -15 + 4 -1x = -15 + 4 Combine like terms: -15 + 4 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11
| (3x^8)(-6)= | | 5x+6=126 | | 3a-3=-11 | | 3-2x=12+7x | | 4a(3a-5b)= | | 5x^2+29-6= | | 5x-y=24 | | -6/7x+15=-33 | | 26x+21=32x-9 | | 3x^2+10x=32 | | 1/9y=-7 | | -4(y-9)=-10(2-y) | | x=4x+2 | | z-1/2=-1/4 | | .3x-4.2=2.4 | | .3-4.2=2.4 | | 60-2x=30 | | 12/18 | | 6-66.6666666667x=-8 | | 19+0+(-9)= | | 6/18+3/19 | | 8/11-4/15 | | 4/9+m=20 | | y=-5x^2+30t+2 | | 2*3*4*5= | | 3x-23=1-4x | | 4/16+2/13 | | 4y+8x=48 | | 3x-2(x+4)=-1 | | 14/15-4/12 | | 5x-11=-11 | | 3/4x+2/9-3/7 |